Prispevek k verodostojnosti podatkov o ustanovitvi čitalnic na Slovenskem - Špendal, Manica (Muzikološki zbornik, 2007)
The musicological debate can not agree about the date of the births of the reading societies in Slovenia. This holds true especially for the foundation of reading societies in Maribor and Ljubljana. Some musicologist are convinced that the birth of National Slavonic Reading Society in Triest (on 29th January 1861) was followed consecutively by foundation of National Reading Society in Ljubljana (on 20th October 1861) and National Slavonic Reading Society in Maribor (on 4th September or on 10th November). However the majority of scholars points out that as the formal foundation date should be considered the day on which the founders confirmed with their signatures the first protocol what happened in Maribor already on 17th July 1861.
Keywords: 19.st.; čitalnice; slovenska glasba; zgodovina glasbe